Incidence, aetiology and serotype coverage for pneumococcal vaccines of community-acquired pneumonia in adults: a population-based prospective active surveillance study in Brazil. Issue 4 (15th April 2022) - Duarte, Fernanda Gross; Barberino, Maria Goreth; da Silva Moreira, Sandra; Reis, Joice Neves; Spinardi, Julia Regazzini; de Almeida, Rodrigo Sini; Allen, Kristen E; Alexander-Parrish, Ronika; Brim, Rosa; de Araújo Neto, César Augusto; Moreira, Edson Duarte
Abstract : Objectives: To determine the incidence, aetiology and pneumococcal serotype distribution of community-acquired pneumonia (CAP) in Brazilian adults during a 2-year period. Design: Prospective population-based surveillance study. Setting: Patients from two emergency hospitals in Brazil were consecutively included in this study. Participants: A total of 111 adults aged 50 years and older with radiographically-confirmed CAP requiring an emergency department visit were prospectively enrolled between January 2018 and January 2020. Main outcome measures: Incidence rates of CAP were calculated according to age and pathogen. Pathogens were identified by conventional microbiological methods. Additionally, a novel, Luminex-based serotype specific urinary antigen detection assay was used to detect serotypes included in pneumococcal vaccines. Results: Mean age of participants was 64 years and 31% were aged ≥70 years. Aetiology was established in 61 (57%) patients; among identified cases, the most common pathogens were Streptococcus pneumoniae (42/61, 69%) and influenza (4/61, 7%). Among serotypes identified from the 42 cases of pneumococcal CAP, estimated coverage ranged by pneumococcal vaccine formulations from 47.6% (13-valent), 59.5% (20-valent, licenced in the USA only) and 71.4% (23-valent). In patients with CAP, 20-valent pneumococcal vaccine serotypes were identified 2.5 times more frequently than 10-valent pneumococcal vaccine serotypes (22.5% vs 9.0%). The incidence rate for CAP in adults aged ≥50 years was 20.1 per 10 000 person-years. In general, the incidence of CAP increased consistently with age, reaching 54.4 (95% CI 36.8 to −76.6) per 10 000 in adults 80 years or older. Conclusions: We observed a high burden of pneumococcal CAP among adults in Brazil. Despite the routine immunisation of children and high-risk adults against pneumococcal disease in the Brazilian national vaccination programme, a persistent burden of pneumococcal CAP caused by vaccine serotypes remains in this population.